The study on the awareness of mentoring program among lecturers: A case study of UNITEN - Saad N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Education; Knowledge management; Program documentation; Surveys; Teaching; Coaching; Higher education; Mentoring; Mentoring programs; Peer monitoring; Teaching and learning; Transfer of knowledge; Engineering education